¿Por qué los españoles «saben» lenguas mientras los polacos tan solo las «conocen»? Los verbos de conocimiento en contraste polaco-español - Zieliński, Andrzej (Studia Romanica Posnaniensia, 2023)
The objective of the study is to delve into the main syntactic and semantic differences and similarities of the so-called verbs of knowledge, that is, the predicates, that denote the cognitive attitude of the sentence subject toward the acquaintance. The author will address the contrastive analysis of the main Spanish verbs –saber, conocer– with the corresponding Polish verbs –wiedzieć, znać, potrafić and umieć.